2020
DOI: 10.12688/f1000research.23783.1
|View full text |Cite
|
Sign up to set email alerts
|

Glycoalkaloids in commercial potato varieties traded in Nairobi, Kenya

Abstract: Background: Glycoalkaloids are naturally occurring toxins in potatoes which, at high levels, pose food safety concerns to consumers. Their concentrations in potatoes are dependent on postharvest handling, variety and stress factors tubers are exposed to. Limited information, however, exists on levels of glycoalkaloids in commercially traded potato tubers in Kenya. The current study sought to determine the glycoalkaloid levels in potatoes traded in Nairobi, Kenya.  Methods: Three potato varieties, Shangi, Dutch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The levels of these inherent GAs are dependent on species, environmental conditions, and management practices. Thus, the GAs found in the untreated tubers that were not stored are characteristics of the shangi potato variety (Musita et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of these inherent GAs are dependent on species, environmental conditions, and management practices. Thus, the GAs found in the untreated tubers that were not stored are characteristics of the shangi potato variety (Musita et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore plausible that the expression of Sgt1 is optimized in a dark store while the expression of Sgt2 is optimized in a store with varying light intensity. This could explain why Musita et al (2020) reported a higher α-chaconine to the α-solanine ratio in shangi potatoes that were exposed to long periods of light.…”
Section: Effects Of Magnetic Field Intensity Under Store Typesmentioning
confidence: 99%